Lysozyme and mucins in gastric adenomas. Issue 8 (August 1989) - Caruso, R A; La Spada, F; Casablanca, G; Rigoli, L
Abstract : A method for the simultaneous demonstration of lysozyme and mucins in 39 cases of gastric adenomas differentiated two intermediate cell types. The first was similar to a columnar cell comprising a single cell population which covered extensive areas of the adenomas. This cell type often showed supranuclear lysozyme reactivity and apical neutral mucins, sialomucins, and sulphomucins in variable amounts. The second cell type was found in 11 adenomas, located mainly in the fundal area. It seemed to be a transitional form between the goblet cell and the Paneth cell. This cell type was scattered among columnar cells, occasional Paneth-like cells, and small goblet cells. These two types of intermediate cells may be regarded as abnormally differentiated integral elements of gastric adenomas. They may be associated with the neck stem cells in the cytogenesis of gastric adenomas.